Leadership Development Community-based Buddhist Doctrines to Prevent Corruption in Chaiyaphum Province - Swadrathand , Narat; Chueram, Wai (Dhammathas Academic Journal, 2020)
The objectives of the research were (1) to study community leadership in Chaiyaphum Province, (2) to develop Buddhism-based leadership against anti-corruption in Chaiyaphum Province, and (3) to analyze Buddhism-based leadership against anti-corruption in Chaiyaphum Province. This was the mixed methods research that advanced the systematic integration of quantitative and qualitative data within a single study. The qualitative data were collected from the study of involved documents and the in-depth interview, and analyzed with the descriptive and inductive statistics. The findings of the research were as follows: 1. The study of community leadership in Chaiyaphum Province was found that, 1) the physical development (kaya-bhavana in Pali) was composed of individuality, enthusiasm, and economic status, 2) the precept development (sila-bhavana in Pali) was comprised of the leader’s self-discipline, the leader’s creation of regulations for the community, and the leader’s honesty, 3) the mental development (citta-bhavana in Pali) consisted of morality and ethics, impatience and endurance, and prudence, 4) the wisdom, which comprised the state of a developer, problem solving without violence, and optimism. 2. The study of development of Buddhism-based leadership against anti-corruption in Chaiyaphum Province was found that, 1) the physical development (Kaya Bhavana) was grown in seven qualities of a good man (Sappurisa Dhamma), 2) the moral development (Sila Bhavana) was flourished in four virtues for lay people (Gharavasa Dhamma), and 3) the mental development (Citta Bhavana) was improved in the Threefold Learning (Sikkha). 3. The analysis of Buddhism-based leadership against anti-corruption in Chaiyaphum Province was found that, 1) in the political aspect, after Buddhism-based leadership had already been developed, self-immunity would prevent the leader from evil deeds and to make him reasonable to ponder and analyze political problems; 2) in the economic aspect, Buddhism-based leaders were proud of their own dignities, and they were not anxious to keep their own fame and their family reputation; and 3) in the social aspect, Buddhism-based leaders were people with viceless shields, who lived their living lives as a role model for the society and were intelligent to solve many problems. Generally, the majority of people often held their community leader as a role model.